2010
DOI: 10.1680/grim.2010.163.2.101
|View full text |Cite
|
Sign up to set email alerts
|

On settlement of stone column foundation by Priebe's method

Abstract: Several contributions have been suggested to estimate the assumed linear elastic settlement of foundations on columnar reinforced soils. A number of authors have considered the so-called Priebe's method, which has been extensively used worldwide, and they have made suggestions especially for soft clays reinforced by stone columns. This paper first offers a critical analysis of the semi-empirical Priebe method by pointing out some inconsistencies related to assumptions made and the theoretical derivation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Ellouze et al (2010) pointed out several inconsistencies of the assumptions made in the method. The present model computes the settlement of the soft ground and considers the volumetric compressibilities of the soil and that of the column using the radial consolidation theory.…”
Section: Parametric Studiesmentioning
confidence: 99%
“…Ellouze et al (2010) pointed out several inconsistencies of the assumptions made in the method. The present model computes the settlement of the soft ground and considers the volumetric compressibilities of the soil and that of the column using the radial consolidation theory.…”
Section: Parametric Studiesmentioning
confidence: 99%
“…Recently, Ellouze et al (2010) have criticized the framework of Priebe's method and have pointed out some inconsistencies related both to the assumptions and to the derivation of improvement ratios to evaluate the reduction in settlement induced by stone column reinforcement.…”
Section: Priebe Methodsmentioning
confidence: 99%
“…Consider the effect of stone column installation by lateral expansion, Ellouze et al [12] reported that an improvement in the Young's modulus of the initial soil takes place due to the horizontal consolidation owed to the presence of stone columns. Then, prior to the final loading due to the construction of oil tank, the averaged improvement in Young's modulus of loose silt sand can attain by 30% around each stone column over a horizontal distance of about 1.5 times its diameter.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The equivalent co-centric crowns (ECC) modeling can be adopted, in case the reinforcing columns are located in a regular pattern as investigated by Ellouze and Bouassida (2009) and Ellouze et al [12]. Major advantage of this geometrical transformation consists in carrying numerical computations in axisymmetric condition that is timeless consuming than 3D modeling.…”
Section: Equivalent Concentric Crowns (Ecc)mentioning
confidence: 99%